"Active Methodologies, An Important Educational Tool In Collaborative Learning In First Year Students In Their Professional Medical Career". - Cristian Manuel Diaz Peña (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study describes the contribution of the active methodology as an important tool in the development of collaborative learning, using different technological didactic methods that seek to provide and/or assume challenges, solve academic-professional problems in an integral and joint way seeking to assume responsibilities to achieve their professional objectives. In this context, the research aims to demonstrate how active methodologies influence the collaborative learning of students in the first year of studies of their professional medical career. This is an experimental-correlational research, with the application of different active methodologies in class, observation cards and different evaluative resources graded individually and in groups to demonstrate the improvement of collaborative learning in the studied population. The sample was formed by 2 groups (group A of 36 students, without the research variables and group B of 32 students, with the dependent and independent variable), during 5 weeks that lasts the unit 3 of the regular cycle, both groups were analyzed and studied at the same time applying the research variables in one and not in the other. From the results obtained in group A at the end of the unit: 28% of students passed and 72% of students failed. The results obtained in group B at the end of the unit 90% of students passed and 10% of students failed, which allowed to affirm that the active methodologies, both in active teaching strategies based on information and communication technologies, significantly influence the collaborative learning of medical students for their development and benefit in the professional environment.